Heurística de economias: um estudo de caso na empresa atox como estratégia de logística de roteirização - GONÇALVES, Altobele Campos (2019)
In this work, the heuristic method of savings of Clarke and Wright, applied as a case study, was proposed as a strategy of routing in order to analyze the client portfolio of the Atox Company located in Belém-Pará. A company that provides services for the dedetization and hygiene of the spaces where the clients look for the processes. The research was characterized as being of a quantitative and qualitative nature, aiming at a study of the routing of the customer's premises so that the teams attenuated the losses from the exit to the place where the services are rendered. Thus, to improve the efficiency of this locomotion to the right purposes, providing an improvement in the moment of delivery, avoiding waste of fuel and time, guaranteeing the delivery of services with greater credibility to these requested clients. The Clarke and Wright method proved that the routes traced by the teams were empirically designed, so they do not take into account the day-to-day factors that led to losses in both time and cost. Through the method, it was visible that there was a gain in time and cost of departure and arrival of the teams to the sites of the daily services, an economy around 62% with fuel based on the method of Clarke and Wright.